Dental care and risk of developing severe COVID-19 - Díaz Arizmendi, Leopoldo Javier (2023)
During the COVID-19 pandemic, dental care was recommended only in urgent and severe pain cases. Reduced dental appointments may affect the financial situation of dentists, especially those who are not financially secure. Due to economic necessity, dentists are required to provide care despite the risk of being infected with SARS-COV-2. Objective: To describe the frequency of dental care and the risk of complications due to COVID-19 among dentists in Ixtlahuaca, State of Mexico, Mexico. Material and methods: Cross-sectional study, non-probabilistic sampling carried out from August to September 2020. A survey was carried out through social networks to identify thefrequency of dental care. Results: The sample consisted of 121 dentists with an average age of 32.3 years. Women comprised most of the sample (74.4%). Dentists had a medium risk of suffering complications due to COVID-19 (92.5%). Private practice dentists performed more non-urgent treatments during the red and orange epidemiological risk periods, showing statistically significant differences (p≤0.05). Unhealthy weight was present in 30% of the sample. Conclusions: Dentists have a medium risk of becoming seriously ill from COVID-19. The risk is associated with unhealthy weight. Dentists performed non-urgent treatments despite government recommendations. Privatepractitioners performed a greater number of non-urgent treatments. Dentists provide care despite epidemiological risk related to COVID-19 due to economic necessity.